Emerging sustainable solutions for depollution: Geopolymers - Asim N.; Alghoul M.; Mohammad M.; Amin M.H.; Akhtaruzzaman M.; Amin N.; Sopian K. (Elsevier Ltd, 2023)
Buildings; Catalysts; Cost effectiveness; Geopolymers; Industrial wastes; Pollution control; Water pollution; Catalytic performance; Depollution; Engineered materials; Light irradiations; Organic pollution; Preparation method; Sustainable; Sustainable solution; Inorganic polymers